Visual Outcome And Complications After Cataract Surgery In Diabetic And Non-Diabetic Patients - Monte, Kawshik Nag; Alam, Md. Shahriar; Tanzin, Tanuja; Sen, Utpal; Basu, Debolina; Aovi, Aovijit Nag (Journal of Chittagong Medical College Teachers' Association, 2026)
Background: Cataracts are a leading cause of visual impairment globally, with higher prevalence and higher risks of complications with variable visual recovery among diabetic patients. The aim of the study is to compare the visual outcomes and postoperative complications of cataract surgery in diabetic versus nondiabetic patients attending Chittagong Medical College Hospital (CMCH). Materials and methods: This prospective comparative study was conducted from January to December 2022 and included two groups: 104 diabetic and 105 nondiabeticpatients.Visual acuity and complications were assessed preoperatively and at 1 week, 1 month and 3 months postoperatively. Data were analyzed using SPSS v25. Results: The diabetic group (n=104) had a significantly lower mean age (56.7±5.7 years) than the non-diabetic group (n=105) (60.4±6.3 years) (p<0.001). Diabetic patients had slightly poorer BCVA at 1 week (0.74 LogMAR) 1 month (0.49 LogMAR) and 3 months (0.30 LogMAR) compared to non-diabetics (0.68, 0.45, 0.27 LogMAR, respectively) though the overall visual gain was evident in both. Intraoperative complications (e.g. posterior capsular rent, vitreous loss) and postoperative complications (e.g. anterior chamber reaction, corneal edema, posterior capsular opacity, cystoid macular edema) were numerically higher in diabetics, but none reached statistical significance. Conclusion: Diabetic patients can achieve similar visual outcomes after cataract surgery, with slightly higher complication rates, but modern surgical techniques remain safe and effective. JCMCTA 2025 ; 36 (2) : 65-70